At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
The option B is correct, The second expression gives the correct value -24.
According to the statement
we have given that the some expression and a = -2 and b = 3 and we have to which expression gives a output of answer -24 after put the values in the expressions.
So, For this purpose
First expression:
[tex]a\sqrt{16} + b - 10[/tex]
Put a = -2 and b = 3
then
[tex]= -2\sqrt{16} + 3 - 10\\= -8 -7\\= 15[/tex]
Second expression:
[tex]a(\sqrt{16} + b) -10[/tex]
Put a = -2 and b = 3
then
[tex]a(\sqrt{16} + b) -10\\-2(4 +3) -10\\-14-10\\-24[/tex]
Now,
Third expression:
[tex]a\sqrt{16} + (b - 10)[/tex]
Put a = -2 and b = 3
then
[tex]a\sqrt{16} + (b - 10)-2*4 + (-7)\\-8-7\\-15[/tex]
Now,
Fourth expression and first expression are same,
So,
Fourth expression:
[tex]a\sqrt{16} + b - 10[/tex]
Put a = -2 and b = 3
then
[tex]= -2\sqrt{16} + 3 - 10\\= -8 -7\\= 15[/tex]
The second expression gives the correct value -24.
So, The option B is correct, The second expression gives the correct value -24.
Learn more about Expressions here
https://brainly.com/question/4344214
#SPJ1
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.